SENGKETA KEPEMILIKAN TANAH SUGUHAN DI DESA SIGARA-GARA BERDASARKAN SK.GUBERNUR SUMUT NO: 16/BPPST/AGR/1961 (STUDI TERHADAP PUTUSAN MA. NO 3418 K/PDT/2015) - NURLYNA SEMBIRING (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhammad Yamin, SH, MS, CN2. Prof. Dr. Syafruddin Kalo, SH, MHum3. Notaris Dr. Tony, SH, MKnLand is an element which cannot be separated from life since it is closelyrelated to human life in various fields. Land dispute causes disagreementamong people since each of them struggles for their interest. The object ofdispute is a piece of land granted by the Governor of North Sumatera at Sigaragaravillage with the letter No. 16/BPPST/Agr/1961. The research problems arehow about the enabling factors of land dispute on granted land ownershipbased on the Supreme Court’s Ruling No. 3418 K/Pdt/2015, how about itsvalidity based on the Directive of the Governor of North Sumatera No.16/BPPST/Agr/1961, and how about the judge’s consideration in the appealbased on the Supreme Court’s Ruling No. 3418 K/Pdt/2015.Keywords: Land Dispute, Granted Land, Plantation Land